The Mediating-Moderating Effects of Job Stress and Organizational Support on the Relationship Between Job Demands Resources and Nurses' Job Performance in Saudi Public Hospitals - Al-Homayan, Abdullah Mohammad (2013)
This study examined the determinants of nurses’ job performance in public hospitals in Saudi Arabia. Specifically, the objectives were: (1) to identify the job performance level of nurses in Saudi Arabia; (2) to examine the relationship between job demands and resources, and nurses’ performance; (3) to investigate the effect of job stress as a mediating variable on the relationship between job demands and resources, and nurses’ performance; and (4) to determine the moderating effect of organizational support on the relationship between job stress and nurses’ performance. The study utilized a survey method and questionnaires which were distributed to a sample of 1,443 nurses at nine hospitals. Several statistical techniques were used including reliability, factor analysis, bivariate correlation analyses, multiple regression, and hierarchical regression analyses. The study found the level of nurses’ job performance to be moderate. Also the study found direct significant relationships among the tested job demands and job resources variables with nurses’ job performance. Moreover, the study found partial support for the role of job stress as a mediator in the relationship between job demands and resources (JD-R) and nurses’ job performance. Job stress mediated the relationship between the job demands resources variables (except job security) and two dimensions of job contextual performance (compliance and volunteering for additional duties). In addition, the study found that organizational support moderated the relationship between job stress and all dimensions of nurses’ job task performance (i.e. provision of information, coordination, provision of support and technical care), and two dimensions of nurses’ job contextual performance (i.e. interpersonal support and volunteering for additional duties). Contributions, limitations, and implications of the study are also discussed.